(untitled) (Global Journal of Human-Social Science, 2017)
The objective of the present research was to study the self-concept as the predictor of imposter phenomenon among the male and female students of Himachal Pradesh University The other objective was to study the self-concept as the predictor of imposter phenomenon among the science and non-science students of Himachal Pradesh University The results showed that self concept is the strong predictor of imposter phenomenon among female students as compared to male students Further the results showed that self concept is the stronger predictor of imposter phenomenon among non-science students as compared to science students